Mechanical and Biological Performance of Titanium Hydroxyapatite Composites for Biomedical Applications - Vincent B. ONIGBARA; Muftau A. GBENLE; Sunday I. AGU (FUDMA Journal of Engineering and Technology, 2026)
Research findings indicate that alloys derived from titanium are widely applied in orthopaedic implants as a result of their good mechanical strength, anti-corrosive property, and biocompatibility. However, their limited bioactivity and mismatch in mechanical behaviour compared to bone often lead to stress shielding and reduced biological performance. This study investigates the mechanical and biological performance of titanium hydroxyapatite composites developed for biomedical applications. Reinforcement was added to titanium alloy powder (Ti6Al4V, 20 µm) using laboratory-prepared hydroxyapatite (5.5 µm) at varying weight percentages (10, 20, 30, and 40 wt% HA) using the powder metallurgy technique. The blended powders were compacted at 200 MPa. Sintering was performed in an argon atmosphere at 1100°C for 2 hours. Density evaluation was performed on the prepared composites using Archimedes’ principle, compressive strength using a digital compression testing machine, and structural morphology analyzed using SEM. Results showed that density decreased with increasing hydroxyapatite content, while sintered materials had increased density relative to unsintered sampless due to consolidation during sintering. There was a drop in compressive strength with increasing HA content, with the 90%Ti6Al4V–10%HA composite exhibiting the maximum recorded compressive strength (23.2 MPa) and the 60%Ti6Al4V–40%HA composite showing the lowest (5.7 MPa). The strength values obtained fall within the range of human trabecular bone (0.1–30 MPa.), indicating suitability for orthopaedic applications. The study concludes that Ti6Al4V/HA composites demonstrate promising potential for biomedical implant applications, although optimization of hydroxyapatite content and porosity is necessary to achieve improved mechanical and biological performance.
Keywords: Titanium, Ti6Al4V; Hydroxyapatite; Powder Metallurgy; biomaterials; porous materials.